Differences in mental index value in patients with type II diabetes mellitus using panoramic radiography - Garcia, Frida Dillenia Contesa; Sarifah, Norlaila; Sukmana, Bayu Indra; Budipramana, Melisa; Sari, Galuh Dwinta (Ikatan Radiologi Kedokteran Gigi Indonesia, 2024)
Objectives: This research is aimed to determine the mandibular cortical thickness by the Mental Index value using panoramic radiography in patients with type 2 DM based on length of suffering ≤ 5 years and > 5 years. Materials and Methods: This research is using unpaired comparative analytical design with a cross-sectional stratified random sampling method and unpaired T-test statistic. Results: 34 samples of patients with type 2 DM showed that the mean mental index was 4.219 ± 1.223. The two groups did not have a difference in the meaning of the MI value. The MI of the group with a shorter history of suffering (≤ 5 years) was 4.227 ± 1.063 and the group with a longer history of suffering (>5 years) was 4.211 ± 1.399. There were 8 people who experienced thinning bone from the whole age group, the most were from the age group of 51-60 years old. Conclusion: Mental Index (MI) value is greater or exceeds the normal value (≥ 3,1 mm) in both groups of patients with type 2 DM based on length of suffering ≤ 5 years and > 5 years. Keywords: Diabetes mellitus type 2, Mental Index, Mandibular Cortical Bone, Panoramic Radiography, Bone Mineral Density.